A novel procedure for endobronchial ultrasound-guided transbronchial mediastinal cryobiopsy with a puncture dilation catheter - Tong, Run; Deng, Mingming; Zheng, Ziwen; Zhou, Guowu; Bian, Yiding; Zhao, Ling; Herth, Felix; Hou, Gang (Respiration, 2024)
Introduction: Endobronchial ultrasound (EBUS)-guided transbronchial mediastinal cryobiopsy (TBMC) is increasingly used to diagnose mediastinal lymphadenopathy. Various methods have been used to create a tunnel between the airway wall and the lesions for this procedure, such as electrocautery and penetration with the sheath of the needle for EBUS-transbronchial fine needle aspiration. However, those methods are complex. Case Presentation: We developed a new technique called EBUS-TBMC via a tunnel, and we used it in four cases of mediastinal and/or hilar lymphadenopathy. We used a puncture dilation catheter to create a tunnel between the airway wall and the target lymph node. The cryoprobe was introduced to the target lymph node and cooled with liquid carbon dioxide for 5-9 s. The probe was subsequently pulled out with the samples to complete the EBUS-TBMC via a tunnel. A definite diagnosis was made based on pathological examination of the samples obtained in all four cases. After the procedure, none of the patients experienced moderate to severe bleeding, pneumothorax, pneumomediastinum, or other adverse events. Conclusion: EBUS-TBMC via a tunnel is a feasible and convenient procedure for the performance of TBMC. Further studies are required to evaluate the safety and efficacy of EBUS-TBMC via a tunnel.
Online veröffentlicht: 30. Juli 2024
Gesehen am 18.06.2025